Sociology of Science and Sociological Metatheory - Petrusek, Miloslav (Teorie vědy / Theory of Science, 2019)
The article surveys the ways science was thematized as a sociological subject. It starts with the reflections on knowledge and science in the Enlightenment, further reviews the main contributions of Comtean philosophy and sociology of science, stresses Merton’s role in making the traditional sociology of knowledge open to empirical research, and traces the subsequent development of the field: the progress of quantitative analyses and ethnographic researches of science, the Kuhnian turn towards historicizing and Foucaultian turn towards the politics of science, the evolution of cognitive sociology of science, as well as the inspirations drawn from works of Bloor, Barnes, and Latour.